A multi-cohort validated OXPHOS signature predicts survival and immune profiles in grade II/III glioma patients - Mou, Jun; Zhang, Min; Qin, Fumin; Cui, Yajie; Xu, Keyou; Pang, Baoye; Li, Xinyue; Tan, Wanyi; Yang, Aiqi; Liu, Yaxin; Shen, Lingjun; Liu, Yanting; et al. (Frontiers in Immunology, 2025)
IntroductionGrade II/III gliomas are invasive brain tumors with a high risk of malignant progression and significant clinical heterogeneity, highlighting the urgent need for reliable prognostic biomarkers to guide personalized treatment strategies. This study aimed to investigate the molecular mechanisms driving glioma progression and to identify potential therapeutic targets.MethodsWe analyzed 200 mitochondrial oxidative phosphorylation (OXPHOS)-related genes in 512 grade II/III glioma samples from The Cancer Genome Atlas (TCGA). Consensus clustering identified two distinct molecular subtypes (C1 and C2). Differentially expressed genes (DEGs) between subtypes were determined using the limma package. The immune cell composition and tumor microenvironment (TME) characteristics were assessed using ESTIMATE, MCPcounter, and CIBERSORT algorithms. Based on prognostic DEGs, we constructed a four-gene prognostic signature (MAOB, IGFBP2, SERPINA1, and LGR6).ResultsThe C2 molecular subtype was associated with poorer prognosis, higher immune scores, and enrichment in tumor-promoting pathways. The four-gene signature demonstrated strong prognostic performance and robustness across multiple independent validation cohorts. Immunohistochemical (IHC) analysis of clinical glioma specimens confirmed elevated protein expression levels of the four genes in tumor tissues.DiscussionOur OXPHOS-associated gene signature provides novel insights into the molecular classification, immune landscape, and prognosis of grade II/III gliomas. These findings lay the foundation for precision oncology and the development of targeted therapeutic interventions.